A modalidade epistêmica em transmissões telejornalísticas ao vivo de extensa duração - Matsumoto, Aline Ramires Moraes (2008)
Modalities and performance of epistemic modalizing agents in three longduration live television newscasts are provided. In the above-mentioned cases journalists have to deal with unforeseen events, lack of information and the need of filtering and broadcasting the news within a short period of time without jeopardizing journalistic ethics. Current research corpus comprises live transmissions on the kidnapping of the Brazilian entrepreneur Silvio Santos, the terrorist attack on the World Trade Center and the Pentagon and the Second Iraqi War, broadcasted by the TV Globo network. The communication effect of epistemic modalizing agents in the three live transmissions is analyzed according to the basic principles of functionality and the methodology of quantitative-qualitative data analysis. Investigation of the above corpus showed that journalists back the news by direct and indirect evidence so that the given information's reliability is reinforced and a truthful quality attributed to the news. Information is thus filtered by the knowledge of journalists, specialists and authorities who are invited to participate in live broadcasts. If these journalists are convinced of the exactness and truthfulness of the events, they modalize their statements to the extreme limits of certitude. On the other hand, if doubts exist on the news contents, they epistemically modalize their statements with degrees of possibility and imprecision markers. The concomitant existence of certitude and incertitude in live newscasts is caused by the type of construction and transmission of news since the occurrence and narration of events are simultaneous in this type of information broadcasting. Analysis also revealed that, when journalists modalize their statements, they comply with the tenets of truth and fidelity insisted on by journalist ethics. Nevertheless, the objectivity principle is subverted since the very epistemically modalized statements demonstrate a production-inherent subjectivity of news within the context of longduration live newscasts.